Sistem Diagnosis Penyakit Tanaman Melon Menggunakan Metode Dempster-Shafer - Dwi Prasetyo; Nurul Hidayat; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Melon plant is a kind of plant that potentially attacked by plant disease. The lack of farmer knowledge in this field for controlling and maintaining the disease can affect the melon fruit productivity and contribute to plant damage. Therefore, the melon production would not achieve the expected target. In addition, another important problem is the higher number of symptom which resulted in difficulties to diagnose the melon plant disease. Basically, the farmer could discuss with the expert in plant pathologist field to control and try to solve this problem. However, this solution still has some limitation. It caused by restriction of the number of expert, long distance away, and it will take more longer time to analyze. The result show that, a system which was developed by using Dempster-Shafer method based on 24 data of melon plant symptom has reached success rate 87,5%. This value was obtained from 21 of 24 experiment data and it assumed as correct data. It was occurred because data that obtained was significantly different from the other data. It could be occurred because of the symptom density have similar weight in different types of disease.